2022
DOI: 10.3389/fvets.2022.874453
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fermented-Moutai Distillers' Grain on Growth Performance, Meat Quality, and Blood Metabolites of Finishing Cattle

Abstract: The present study evaluated the effect of dietary supplementation with fermented-Moutai distillers' grain (FMDG) on the growth performance, meat quality, amino acid composition and blood metabolites of finishing cattle. Thirty cattle (2 years old; 237.55 ± 10.72 kg) were randomly assigned to one of three dietary supplementations: 0% FMDG (control), 15% FMDG (R1) and 30% FMDG (R2) [dry matter (DM) basis]. After 60 days, the inclusion of FMDG had no significant (p > 0.05) effects on the growth performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…Studies have shown that when the body's IgG or IgA is increased, it can boost the body's immunity [33,34]. The present study has shown that adding PFDG to the basal diet can increase the level of IgA and promote improved immunity in finishing cattle [35]. In our study, it was found that compared with the Control group, the serum IgA and IgG levels of finishing cattle fed with PFDG were higher, indicating that PFDG improved their immunity, a result which was consistent with that of Cheng et al [35].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Studies have shown that when the body's IgG or IgA is increased, it can boost the body's immunity [33,34]. The present study has shown that adding PFDG to the basal diet can increase the level of IgA and promote improved immunity in finishing cattle [35]. In our study, it was found that compared with the Control group, the serum IgA and IgG levels of finishing cattle fed with PFDG were higher, indicating that PFDG improved their immunity, a result which was consistent with that of Cheng et al [35].…”
Section: Discussionsupporting
confidence: 54%
“…The present study has shown that adding PFDG to the basal diet can increase the level of IgA and promote improved immunity in finishing cattle [35]. In our study, it was found that compared with the Control group, the serum IgA and IgG levels of finishing cattle fed with PFDG were higher, indicating that PFDG improved their immunity, a result which was consistent with that of Cheng et al [35]. IL-10 itself can repress proinflammatory responses and limit unnecessary tissue disruptions caused by inflammation [36].…”
Section: Discussionmentioning
confidence: 57%
“…The DGs used in this study were from Kweichow Moutai Company Limited (Renhuai, China). The main ingredients of Moutai DG are distilled sorghum and wheat, which are a byproduct of the brewing processes [14]. The microbial starter is from Yijiayi Bioengineering (Shijiazhuang, China), mainly composed of Bacillus, Lactobacillus, Saccharomyces, and Bifidobacterium, as well as various compound enzyme preparations such as amylase, protease, cellulase, and lipase.…”
Section: Preparation Of Fdgmentioning
confidence: 99%
“…Previous studies have mainly focused on the effects of FDG on the growth performance, feed conversion, and digestibility of livestock and poultry. Our previous studies also showed that adding 30% FDG to the diet did not affect the growth performance, meat quality, and blood metabolism of fattening cattle [14]. However, there is a lack of information on the effects of dietary fermented distiller's grains supplementation on the gastrointestinal microbiota and metabolites of beef cattle.…”
Section: Introductionmentioning
confidence: 95%
“…Механизмы такого влияния представлены в работе R. N. Tamddondoust, Y. Wang, M. Jafarnejad, T.E. Graber [9], в частности описан процесс перепрограммирования синтеза белков клетки в ответ на высокие дозы ионизирующего излучения.…”
unclassified